The effect of post-traumatic stress disorder on refugees' parenting and their children's mental health: a cohort study. (May 2018) - Bryant, Richard A; Edwards, Ben; Creamer, Mark; O'Donnell, Meaghan; Forbes, David; Felmingham, Kim L; Silove, Derrick; Steel, Zachary; Nickerson, Angela; McFarlane, Alexander C; Van Hooff, Miranda; Hadzi-Pavlovic, Dusan
Summary: Background: Children and adolescents, who account for most of the world's refugees, have an increased prevalence of psychological disorders. The mental health of refugee children is often associated with the severity of post-traumatic stress disorder (PTSD) in their caregivers. Despite the potential for refugee caregivers' PTSD to affect child mental health, little evidence exists concerning the underlying mechanisms of this association. This study tested the effect of refugee caregivers' previous trauma and levels of ongoing stressors on current PTSD, and in turn how this influences parenting behaviour and consequent child psychological health. Methods: This cohort study recruited participants from the Building a New Life in Australia study, a population-based prospective cohort study of refugees admitted to 11 sites in Australia between October, 2013, and February, 2014. Eligible participants were aged 18 years or older and the principal or secondary applicant (ie, the refugee applicant within a migrating family unit) for a humanitarian visa awarded between May, 2013, and December, 2013. Primary caregiver PTSD and postmigration difficulties were assessed at Wave 1 (in 2013), and caregiver PTSD was reassessed at Wave 2 (in 2014). At Wave 3, between October, 2015, and February, 2016, primary caregivers repeated measures of trauma history, postmigration difficulties, probable PTSD, and harsh and warm parenting style, and completed the Strengths and Difficulties Questionnaire for their child. We used path analysis to investigate temporal patterns in PTSD, trauma history, postmigration stressors, parenting style, and children's psychological difficulties. Findings: The current data comprised 411 primary caregivers who provided responses in relation to at least one child (660 children). 394 primary caregivers with 639 children had data on independent variables and were included in the final model. Path analyses revealed that caregivers' trauma history and postmigration difficulties were associated with greater subsequent PTSD, which in turn was associated with greater harsh parenting and in turn, higher levels of child conduct problems (β=0·049, p=0·0214), hyperactivity (β=0·044, p=0·0241), emotional symptoms (β=0·041, p=0·0218), and peer problems (β=0·007, p=0·047). There was also a direct path from primary caregiver PTSD to children's emotional problems (β=0·144, p=0·0001). Interpretation: PTSD in refugees is associated with harsh parenting styles, leading to adverse effects on their children's mental health. Programmes to enhance refugee children's mental health should account for PTSD in parents and caregivers, and the parenting behaviours that these children are exposed to. Funding: National Health and Medical Research Council.